The Dukuns of Madura: Their Types and Sources of Magical Ability in Perspective of Clifford Geertz and Pierre Bourdieu - Haryanto, Bangun Sentosa D. (UI Scholars Hub, 2015)
This descriptive paper is based on a research in Madura, Indonesia, in 2014. The research data was mostly through in-depth qualitative interviews and direct observation that have been developed into ethnographic case study. These methods were informed by a methodological approach derived from the ‘structural constructivism’ of Pierre Bourdieu. The main concept of “dukun” (supernatural/magic service providers) of Clifford Geertz was employed to theorize the findings and frame the argument. Within eight-month research period in Madura, I interviewed 19 dukuns and describe them using pseudo-names. Madura’s dukun phenomenon demonstrates that magic is undoubtedly one of the main strategic resources available for mobilization in Madura to gain social/economical and political standing within society. Moreover, due to the fact that Madura is known as one of the most devoted Islamic Area Strictestin Indonesia, it is important to find out how dukuns’ magical ability actually comes into being and is performed.